Customer relationship management as business strategy appliance: Theoretical and practical dimensions - Tamošiūnienė, Rima; Jasilionienė, Regina (Journal of Business Economics and Management, 2007)
The main purpose of this article is to provide an integral and managerially useful view of customer relationship management (CRM) as business strategy. The key objectives are: to analyze CRM origins, development and changes that have occurred over time and to provide its future directions, to rank the variety of CRM definitions and determine CRM definition, which reflects CRM essence most accurately, to analyze components of CRM, to provide a framework, which ensures that CRM is approached on a strategic, balanced and integrated basis, to determine CRM strategy definition, and to identify CRM strategy position in the whole of companies strategies. The article provides best practices of CRM strategy appliance. The methods used: analysis and generalization of scientific and practical works and statistical data. First Published Online: 14 Oct 2010